FACTORS AFFECTING CITIZEN'S PARTICIPATION IN THE BUSINESS INCUBATION PROGRAM IN THE CITY OF SURABAYA - Utomo, Priyo; Dharmawan, Arif; Handoko, Rudy; Raza, Muzammil; Sandyawati, Novi Sri (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The government's efforts in developing the economy of low-income communities in the city of Surabaya require high participation support. The low community participation in the incubation facilitation program for independent businesses is a problem that needs a solution. The purpose of this study was to analyze the factors that influence citizen participation in the business incubation facilitation program in the city of Surabaya. The research method used is descriptive quantitative and case study methods. Data collection techniques using a questionnaire. The analysis technique uses inferential analysis and cross tabs. The results of this study indicate that the results of data processing indicate that individual psychological conditions and stakeholder involvement have a positive effect on citizen participation in the business incubation program in the city of Surabaya with a significance of 0.000, where the value is 0.000 < 0.05. Practical implications, as input to the government as material for evaluating policies on economic empowerment programs to improve the economy of low-income communities in the city of Surabaya. Theoretical implications, as a reference for further theoretical studies of researchers regarding the ladder of participation in the scope of the program